PEMBELAJARAN BERMUATAN DISPOSISI MATEMATIKA PADA KELAS X PROGRAM IPS - Ismunandar, Denni (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
The purpose of this study was to determine the effectiveness of the model of Problem Based Learning (PBL) charged disposition of mathematics and mathematical communication skills in class X IPS program. Selection  of  a  random  sample  run  private and X IPS chosen as an experimental class 4 and  class  X  IPS  3  as  the  control  class. Results from this study is there a strong influence among the disposition mathematics and mathematical communication in improving problem-solving skills in students. On average problem-solving abilities higher than the experimental class problem-solving abilities in the control class.